Challenging Education in the Ottoman Greek Female Journals (1845-1907): a Declining Feminist Discourse (Knjiženstvo, časopis za studije književnosti, roda i kulture, 2023)
The paper’s intention is to present how Ottoman Greek women challenged social inequalities through press, during the Tanzimat period and up to the 1908 Constitutional Reform. The study is based on three journals published in Istanbul, namely Kypseli (1845), Eurydice (1870-1873) and Bosporis (1899-1907), and focused on the journals’ discourses on education inequalities. The debates on women’s education, the argumentation and philosophical platforms provided, illustrate the changing contents of the notions like “equality”, “inequality”, “social injustice” and “female emancipation”. The paper will try to evince the impact of the changing ideologies and political events/circumstances on the changing content of the educational debates and on the declining “feminist” discourse, reflected in the aforementioned journals.
Keywords: women’s education; women’s press; journals; feminisms; Ottoman Empire